Eksplorasi Kemampuan Berpikir Metaforis Matematis Siswa dalam Pembelajaran Creative Problem Solving - Latifah, Annisa; Syaiful, Syaiful; Alghadari, Fiki (Media Pendidikan Matematika, 2025)
Mathematical metaphorical thinking ability is essential for students to transform abstract concepts into more concrete ideas, thereby facilitating in-depth understanding and connections between mathematical topics. This research aims to explore of mathematical metaphorical thinking ability of eighth-grade students when they engage in the Creative Problem Solving (CPS) learning process. The CPS model was chosen because its structured thinking stages especially the Idea Finding phase are expected to trigger a strong divergence thinking process in metaphor formation. This study used a qualitative approach with eighth-grade students as the purposefully selected subjects. Data were collected through a mathematical metaphorical thinking ability test instrument followed by semi-structured interviews to identify the level and type of metaphors used. The results of the analysis show that the CPS learning environment successfully activated and mapped the use of various mathematical metaphors in students. Students who showed high metaphorical ability tended to construct more original and relational metaphors, which played an important role in complex problem-solving. Conversely, students with moderate ability mostly used conventional or functional-structural metaphors to clarify initial understanding. The conclusion of this study confirms that the integration of CPS is an effective strategy for identifying and honing the potential for mathematical metaphorical thinking in junior high school students, providing a basis for improving mathematics teaching strategies centered on creativity.